Neuron-specific enolase and Tau protein as biomarkers for sepsis-associated delirium: a cross-sectional pilot study - Pinto, Agnes Araújo Sardinha; Carvalho, Maira Mello De; Santos, Juliana Bahia; Silva, Rebeca Souza Da; Barbeiro, Hermes Vieira; Gómez, Luz Marina Gómez; Maia, Ian Ward Abdalla; Marchini, Júlio Flávio Meirelles; Garcez, Flávia Barreto; Avelino-silva, Thiago Junqueira; Soler, Lucas De Moraes [UNESP]; Mochetti, Matheus Menão; et al. (Instituto Israelita de Ensino e Pesquisa Albert Einstein, 2025)
In this study, Pinto et al. identified significantly higher levels of neuron-specific enolase and Tau protein in older patients with sepsis-associated delirium in the emergency department, suggesting the potential of these biomarkers as diagnostic tools in this population.

■ Biomarkers of brain injury, such as neuron-specific enolase and Tau proteins, are higher in older patients with sepsis and delirium. ■ Diagnosing sepsis in patients with delirium can be challenging. ■ Early identification of sepsis is key to managing sepsisassociated delirium.
Keywords: Biomarkers; Delirium; Emergency medicine; Neuroinflammatory diseases; Sepsis